2019
DOI: 10.5479/si.0077-5630.624
|View full text |Cite
|
Sign up to set email alerts
|

Stomatopod Crustaceans from Mayotte Island (Crustacea, Hoplocarida)

Abstract: A collection of stomatopods assembled during the KUW 2009 expedition to Mayotte Island and deposited in the Muséum national d’Histoire naturelle Paris is studied with a review of previous records from Comoros and Mayotte Island. In total 14 species are recognized 3 of them being new records for this region. A brief comparison with other regions studied for stomatopods indicates that sampling is still insufficient in Comoros and Mayotte and that dozens of species remain to be inventoried in that region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…One of the diagnostic character of G. ternatensis is an undivided knob on the telson (Manning 1995), but Ahyong (2001), which indicated that some specimens from Cocos-Keeling Islands have a dorsally indented telson knob that gives them a bilobed appearance. Poupin et al (2019) reported specimens from Mayotte with a divided telson knob. In our specimens (all males), three males (RUMF-ZC-6537, 6539, 6899) also possessed divided (or dorsally indented) telson knob (Fig.…”
Section: Remarksmentioning
confidence: 99%
“…One of the diagnostic character of G. ternatensis is an undivided knob on the telson (Manning 1995), but Ahyong (2001), which indicated that some specimens from Cocos-Keeling Islands have a dorsally indented telson knob that gives them a bilobed appearance. Poupin et al (2019) reported specimens from Mayotte with a divided telson knob. In our specimens (all males), three males (RUMF-ZC-6537, 6539, 6899) also possessed divided (or dorsally indented) telson knob (Fig.…”
Section: Remarksmentioning
confidence: 99%
“…Une autre mission importante pour Mayotte, dédiée spécifiquement aux Crustacés, est l'expédition KUW 2009 organisée par J.-M. Bouchard en collaboration avec le MNHN incluant des récoltes à terre, sur le littoral, et en plongée dans le lagon jusqu'à 50 m. La collection de cette mission comprend plus d'un millier de spécimens tous déposés et enregistrés au MNHN. Ils correspondent à plus de 360 espèces distinctes déterminées et publiées régulièrement pendant la décennie qui a suivi la campagne (Macpherson & Cleva 2010 ;Li et al 2012 ;Bouchard et al 2013 ;Poupin et al 2013aPoupin et al , 2018Poupin et al , 2019. Dans ce contexte, la faune des Crustacés Décapodes et Stomatopodes de Mayotte semble a priori assez bien étudiée.…”
Section: Introductionunclassified